Comparative study on anterior cruciate ligament reconstruction: determination of isometric points with and without navigation - Fabio J. Angelini; Roberto F. M. Albuquerque; Sandra U. Sasaki; Gilberto L. Camanho; Arnaldo J. Hernandez (Clinics, 2010)
OBJECTIVES: To compare the accuracy of tunnel placement and graft isometry for anterior cruciate ligament reconstruction performed using a computer-assisted navigation system (Orthopilot) and using traditional instruments. METHODS: The anterior cruciate ligament was removed intact from 36 pairs of human cadaver knees. From each pair, one knee was randomized to Group 1 (conventional) and the other to Group 2 (Orthopilot). An inelastic suture was then passed through the central points of the tibial and femoral tunnels. Neither of the tunnels was drilled. All knees were then dissected, and six parameters were obtained: distances from the tibial tunnel center to the 1) posterior cruciate ligament, 2) anterior horn of the lateral meniscus and 3) medial tibial spine; 4) distance from the femoral tunnel center to the posterior femoral cortex; 5) femoral tunnel coronal angle; and 6) variation of the distance from the femoral to the tibial tunnel with the knee extended and at 90 degrees of flexion. RESULTS: The variation of the distance from the femoral to the tibial tunnel during flexion and extension was smaller in the Orthopilot group (better isometry) compared to the conventional group. There were no statistical differences in any other parameters between the groups, and all tunnels were considered to be in satisfactory positions. DISCUSSION: The results obtained for anterior cruciate ligament reconstruction depend on precise isometric point positioning, and a navigation system is a precision tool that can assist surgeons in tunnel positioning. CONCLUSION: No differences in tunnel position were observed between the groups. Nonetheless, better isometry was achieved in the Orthopilot group than with conventional instruments.